IMPLEMENTASI PENINGKATAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN SKI MELALUI MEDIA AUDIO VISUAL DI MAN 5 GENUKWATU NGORO JOMBANG - Devita Aprillia; Burhanuddin Ridlwan (Millatuna: Jurnal Studi Islam, 2024)
Varying media as a device or strategy that can be used by an educator in developing learning experiences. This media is centered on sound and images. Teachers use this media with the aim of increasing students' interest and enthusiasm for learning. Audiovisual media can attract students' interest, especially if used in SKI subjects that relate to history and past events in practice. By using this media students can minimize boredom. Therefore, educational institutions and teachers must strive to utilize this media in the learning process. Researchers determined 3 research focuses, including: 1). What is the form of audio visual media at MAN 5 Genukwatu Ngoro Jombang, 2). How to implement audio visual media to motivate student learning in SKI subjects at MAN 5 Genukwatu Ngoro Jombang, 3). What are the supporting and inhibiting factors in the use of audio-visual media in the SKI class XI MIPA 1 subject at MAN 5 Genukwatu Ngoro Jombang. In line with the title of the research, the researcher applied a case study type of research with a qualitative approach in his research. Researchers collect the necessary data through field observations, interviews with related sources, and evidence that supports the validity of the data through data documentation if necessary. Researchers achieved the following research results: 1). Class XI MIPA 1 SKI learning activities are held once a week on Mondays for 2 hours (90 minutes). When SKI lessons in class XI MIPA 1 use media or learning tools in the form of audio visuals. LCDs, projectors and speakers are often used as media. 2). By using audiovisual media, we can make students more interested in the programs being broadcast, such as films, pictures, PPT designs, etc. By showing films that are specifically related to the material being discussed, students can eliminate boredom. 3). Supporting factors for the use of audiovisual media in learning activities, first, teacher training in the use of learning media carried out by madrasa heads. The second factor is the availability of the necessary facilities. The first inhibiting factor is that there are no computers available in each class so that teachers can easily use the learning media. The second factor, if there is a clash of voices from other classes, can interfere with the explanation of the video being shown.